2018
DOI: 10.1016/j.prp.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Expression and location of IL-17A, E, F and their receptors in colorectal adenocarcinoma: Comparison with benign intestinal disease

Abstract: The research aimed to investigate secretion, expression and location of IL-17 relative ligands, IL-17 relative receptors, infiltrating inflammatory cells and parenchymal structural cells in colorectal cancer (CRC) compared with ulcerative colitis (UC) and benign hyperplastic polyp. 29 human intestinal tissues with CRC, 17 with UC and 7 with polyp were stained using immunohistochemistry to evaluate immunoreactivity for IL-17 family relative ligands including IL-17A, E, F and their respective relative receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…The level of expression of proinflammatory IL-17A and its receptor IL-17RA has been found to be significantly higher in UC and in benign gut polyps than in CRC. The levels of other ligands from the IL-17 family (E/F) and IL-17RB receptors, along with neutrophil and mast cell infiltration, were significantly reduced in cancer compared to benign lesions, unlike the IL17RC ligand, which together with CD3 + cell infiltration was more highly expressed in CRC than in polyps [217]. The levels of other cytokines may also change.…”
Section: Inflammatory Bowel Diseases and Colorectal Cancermentioning
confidence: 99%
“…The level of expression of proinflammatory IL-17A and its receptor IL-17RA has been found to be significantly higher in UC and in benign gut polyps than in CRC. The levels of other ligands from the IL-17 family (E/F) and IL-17RB receptors, along with neutrophil and mast cell infiltration, were significantly reduced in cancer compared to benign lesions, unlike the IL17RC ligand, which together with CD3 + cell infiltration was more highly expressed in CRC than in polyps [217]. The levels of other cytokines may also change.…”
Section: Inflammatory Bowel Diseases and Colorectal Cancermentioning
confidence: 99%
“…Thus, any potential biomarkers for predicting the prognosis and malignancy of the disease are worth to be investigated. Our previous studies proved that elevated expression of IL-17A was observed in tissues derived from bladder cancer, prostate cancer and rectal carcinoma [5,23,24] suggesting that this cytokine may promote occurrence and development of malignant diseases.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, the release of IL-17A by CEA-specific T cells after CRC surgery does not seem responsible for the poorer survival of those patients [ 146 ]. On the contrary, IL-17F expression seems to be usually downregulated in CRC cells [ 147 , 148 ]. Omrane et al reported that the wildtype IL17F gene was associated with longer OS in CRC patients [ 149 ].…”
Section: The Mediatory Role Of Interleukins In Colorectal Carcinogenesismentioning
confidence: 99%